The Paderborn University BSP (PUB) Library - Design, Implementation and Performance - Bonorden, Olaf; Rieping, Ingo; von Otte, Ingo; Juurlink, Bernhardus
The Paderborn University BSP (PUB) library is a parallel C library based on the BSP model. The basic library supports buffered and unbuffered asynchronous communication between any pair of processors, and a mechanism for synchronizing the processors in a barrier style. In addition, it provides routines for collective communication on arbitrary subsets of processors, partition operations, and a zero-cost synchronization mechanism. Furthermore, some techniques used in the implementation of the PUB library deviate significantly from the techniques used in other BSP libraries.

Geometric Searching in Walkthrough Animations with Weak Spanners in Real Time - Fischer, Matthias; Lukovszki, Tamás; Ziegler, Martin (Algorithms — ESA’ 98)
We study algorithmic aspects in the management of geometric scenes in interactive walkthrough animations. We consider arbitrarily large scenes consisting of unit size balls. For a smooth navigation in the scene we have to fulfill hard real time requirements. Therefore, we need algorithms whose running time is independent of the total number of objects in the scene and that use as small space as possible. In this work we focus on one of the basic operations in our walkthrough system: reporting the objects around the visitor within a certain distance. Previously a randomized data structure was presented that supports reporting the balls around the visitor in an output sensitive time and allows insertion and deletion of objects nearly as fast as searching. These results were achieved by exploiting the fact that the visitor moves ''slowly'' through the scene. A serious disadvantage of the aforementioned data structure is a big space overhead and the use of randomization. Our first result is a construction of weak spanners that leads to an improvement of the space requirement of the previously known data structures. Then we develop a deterministic data structure for the searching problem in which insertion of objects are allowed. Our incremental data structure supports O(1+k) reporting time, where k is a certain quantity close to the number of reported objects. The insertion time is similar to the reporting time and the space is linear to the total number of objects.

A Network Based Approach for Realtime Walkthrough of Massive Models - Fischer, Matthias; Lukovszki, Tamas; Ziegler, Martin (Algorithm Engineering, 2nd International Workshop, WAE '98)
New dynamic search data structures developed recently guarantee constant execution time per search and update, i.e., they fulfil the real-time requirements necessary for interactive walkthrough in large geometric scenes. Yet, superiority or even applicability of these new methods in practice was still an open question. Their prototypical implementation presented in this work uses common libraries on standard stations and thus represents a first strut to bridge this gap. Indeed our experimental results give an indication on the actual performance of these theoretical ideas on real machines and possible bottlenecks in future developments. By special algorithmic enhancements, we can even avoid the otherwise essential preprocessing step.

Multimediale Entdeckungsreisen unserer Welt mit dem Internet - Ziegler, Martin; Fischer, Matthias; Lukovszki, Tamás
Preis für den Beitrag "Multimediale Entdeckungsreisen unserer Welt mit dem Internet"

On Periodic Comparator Networks - Oesterdiekhoff, Brigitte

Universal Continuous Routing Strategies - Scheideler, Christian; Vöcking, Berthold (Theory Comput. Syst.)

Efficient Communication Strategies for Ad-Hoc Wireless Networks (Extended Abstract) - Adler, Micah; Scheideler, Christian (SPAA)

Improved Bounds for Acyclic Job Shop Scheduling (Extended Abstract) - Feige, Uriel; Scheideler, Christian (STOC)

Universal Routing Strategies for Interconnection Networks - Scheideler, Christian

Routing on networks of optical crossbars - Meyer auf der Heide, Friedhelm; Schröder, Klaus; Schwarze, Frank (Theoretical Computer Science)